2023
DOI: 10.1177/17585732231172166
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for rotator cuff tendinopathy: Proposed mechanisms of recovery

Abstract: Rotator cuff (RC) tendinopathy is a common recurrent cause of shoulder pain, and resistance exercise is the first-line recommended intervention. Proposed causal mechanisms of resistance exercise for patients with RC tendinopathy consist of four domains: tendon structure, neuromuscular factors, pain and sensorimotor processing, and psychosocial factors. Tendon structure plays a role in RC tendinopathy, with decreased stiffness, increased thickness, and collagen disorganization. Neuromuscular performance deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 226 publications
(326 reference statements)
0
7
0
Order By: Relevance
“…Outcomes in the qualitative sub-study will be interviews which focus on themes such as motivating factors and barriers to training, empowerment, and explanatory factors [ 46 , 47 ]. During the process, the material can be supplemented if important concepts and themes were not included in the developed interview guide and if new facets of the research question arise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Outcomes in the qualitative sub-study will be interviews which focus on themes such as motivating factors and barriers to training, empowerment, and explanatory factors [ 46 , 47 ]. During the process, the material can be supplemented if important concepts and themes were not included in the developed interview guide and if new facets of the research question arise.…”
Section: Discussionmentioning
confidence: 99%
“…The PASE program was developed with special emphasis on patient responsibility and self-management. Thus, part of the intervention in both groups is that participants are offered patient education including load management, advice to gain an understanding of the relation between the occupational demands/situation, sport/leisure time activities, and shoulder training including skills to perform specific shoulder exercises [ 46 ]. Finally, patients are provided with knowledge on how to act if shoulder pain occurs during home exercise and activities of daily living.…”
Section: Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Evangelidis et al demonstrated that muscle fatigue significantly impacts the stiffness of the biceps femoris long-head muscle more than the semitendinosus and semimembranosus muscles, providing insight into the increased vulnerability to strain injuries within this muscle group [ 8 ]. Additionally, in the context of rehabilitation following Rotator Cuff tendinopathy, there is a manifestation of reduced tendon stiffness [ 9 ].…”
Section: Introductionmentioning
confidence: 99%